THE INFLUENCE OF FINANCIAL LITERACY ON INVESTMENT INTEREST WITH FINANCIAL BEHAVIOR AS A MODERATING VARIABLE - Tarjono, Tarjono; Atiqah, Raden Roro; Utami, Eva Yuniarti; Herawati, Herawati; Anggraini, Asterina (ITB AAS Indonesia Surakarta, 2025)
ABSTRACTThis research is a quantitative study with an explanatory approach. The data used in this article is primary data that researchers obtained from various credible sources and have been used in every existing study. The primary data obtained by the study came from 300 employees of PT Sampurna spread throughout Indonesia. The researcher distributed an online questionnaire containing 10 questions from four statements. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Financial Literacy variable can have a positive relationship direction and a significant influence on the Investment Interest variable, namely 0.016 which is smaller than 0.05. This is because good Financial Literacy can make employees' thinking good and ultimately interested in investing. The next hypothesis also shows the same results that the Financial Behavior variable can moderate the influence of the Financial Literacy variable on the Investment Interest variable. This is because the P-Values are positive and below the significance level of 0.05, namely 0.000 which is smaller than the direct test of 0.016. Thus, the first and second hypotheses in this article can be accepted.Â Â Keywords: Investment Interest, Financial Literacy, Financial Behavior